Report on professional attachment with Civil Aviation Authority of Singapore. - Lim, Bee Ang. (2009)
The purpose of this report is to summarize the business training experience I had during my Professional Attachment in Commercial Division of Civil Aviation Authority of Singapore (CAAS). I will also highlight on one particular aspect of the training that I found most stimulating. In general, I helped the Commercial Division in retail planning, retail operations, rental, customer services, leases, charges and promotions. The most stimulating job is the re-designing of questionnaire in CAAS's Air Passenger Survey Report For Quarter 4, 1994. The existing questionnaire that was prepared by Forbes Research Pte Ltd is found to be too lengthy. I was supposed to make it more concise by changing the structure of some questions.